Tatak Pilipino [episode no. 46]. ([Quezon City ABS-CBN, 1991)
A unique display of Pilipino ways and style.
History of advertising (10 min.) -- Filipinization of advertising (15 min.) -- 10 Most memorable commercials of all times (5 min.) -- Mascots in advertising (10 min.) -- High tech advertising (10 min.) -- Conversation with AD people (10 min.)
In English and Pilipino.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Advertising -- Philippines; Advertising agencies -- Philippines; Adveritising -- Computers